Automatic Smart Street Light - Zullkuffli, Mohamad Hakimi (Multidisciplinary Applied Research and Innovation, 2022)
Automatic Smart Street Light using solar is an efficient way of lowering energy consumption since there are some street lights that do not work well where it is often observed that even after sunrise, the street lights are still ON and causing a major waste of electricity. The purpose of this research is to develop a prototype of an Automatic Smart Street Light system and to study the energy saving.  The scope of this study is Smart Street Light used solar panel to save the electricity consumption and work when there is precense of vehicles or pedestrians. This project requires solar panel,  rechargeable battery, Nodemcu Lolin Baseboard WIFI Development Board ESP 8266 Serial Port modem controller, relay module, LDR sensor and IR sensor. Each of this component will performing specific operations such as manage the street light system, also detect motion of vehicles or pedestrians and the power consumption analysis.  This intelligent system shows that it is suitable for both urban or rural area that helps cost savings to be an energy saving era and give advantages in humanity.